KESIAPAN MENIKAH PADA DEWASA MUDA DAN PENGARUHNYA TERHADAP USIA MENIKAH - Sari, Fitri; Sunarti, Euis (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2013)
This study aimed to analyze marriage readiness factors among young adults and to analyze its influences on the marriage age. Samples in this study were 110 college students. Qualitative data of marriage readiness was analyzed using content analysis approach, revealed seven factors that are emotional, role, financial, social, age, spiritual, and sexuality readiness. Quantitative data of marriage readiness was analyzed by using analysis factor, and revealed ten factors that are emotional control, empathy ability, financial, role, age, and sexuality readiness, communication skill, social ability, social cognitive, and tolerance. Based on the two analysis, marriage readiness factors among young adults were emotional (emotional control and empathy), social (social ability, social cognitive, and tolerance), role, communication, age, financial, and sexual. Marriage readiness between male dan female was different, for male the most important was financial readiness, but female was emotional readiness. Ideal marriage age for male was 26,3 and for female was 23,9 years old, but expected age to marriage of male was 26,1 and female was 24,2 years old. Statistic regression analysis showed that marriage readiness influence the marriage age. The increasing of empathy ability and financial readiness influenced on increasing age of marriage. Meanwhile, the increasing of age readiness, sexuality, and communication ability influenced on the decreasing of marriage.